2015
DOI: 10.1175/jamc-d-15-0012.1
|View full text |Cite
|
Sign up to set email alerts
|

Linear Depolarization Ratios of Columnar Ice Crystals in a Deep Precipitating System over the Arctic Observed by Zenith-Pointing Ka-Band Doppler Radar

Abstract: This study demonstrates that linear depolarization ratio (LDR) values obtained from zenith-pointing Ka-band radar Doppler velocity spectra are sufficient for detecting columnar ice crystals. During a deep precipitating system over the Arctic on 7 December 2013, the radar recorded LDR values up to −15 dB at temperatures corresponding to the columnar ice crystal growth regime. These LDR values were also consistent with scattering calculations for columnar ice crystals. Enhancements in LDR were suppressed within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 43 publications
10
80
0
Order By: Relevance
“…The detected temperature range of −8 to −6 • C corresponds to the growth regime of needles at that height (Pruppacher and Klett, 1996). As (Aydin and Walsh, 1999;Matrosov et al, 2001;Oue et al, 2015b). The simulated L DR values span a range from −16 to −12.5 dB that is in good agreement with the observed sL DR values in the spectrogram that reach values up to −17 dB in Fig.…”
Section: Case 1: Aggregation Of Needles 10:09-10:18 Utcsupporting
confidence: 80%
See 1 more Smart Citation
“…The detected temperature range of −8 to −6 • C corresponds to the growth regime of needles at that height (Pruppacher and Klett, 1996). As (Aydin and Walsh, 1999;Matrosov et al, 2001;Oue et al, 2015b). The simulated L DR values span a range from −16 to −12.5 dB that is in good agreement with the observed sL DR values in the spectrogram that reach values up to −17 dB in Fig.…”
Section: Case 1: Aggregation Of Needles 10:09-10:18 Utcsupporting
confidence: 80%
“…This temperature corresponds to a needle or column generation regime, as in Case 1. In addition, the sL DR -spectrogram observed with Mira shows similar signatures with sL DR -values of −17 dB that agree to the simulation signatures for needles or columns (Aydin and Walsh, 1999;Matrosov et al, 2001;Oue et al, 2015b). Because the cloud conditions are not homogeneous, the hypothesis of the presence of needles is mainly built upon the radiosonde data.…”
Section: Case 1: Aggregation Of Needles 10:09-10:18 Utcsupporting
confidence: 72%
“…This temperature corresponds to a needle or column generation regime, as in Case 1. In addition the sL DR -spectrogram shows similar signatures with sL DR -values of 20 −17 dB that agree to the simulation signatures for needles or columns (Aydin and Walsh, 1999;Matrosov et al, 2001;Oue et al, 2015b). Therefore, it is expected that the enhanced Z DR signature is caused by needles or columns.…”
supporting
confidence: 84%
“…Because radar Doppler velocities are related to particle fall speeds and vertical air motions, multimodality of the Doppler spectra indicates different particle populations coexisting in the radar sampling volume. The multimodal radar Doppler spectra have often been used to infer the presence of mixed‐phase conditions in deep precipitating ice clouds (e.g., Luke et al, ; Oue, Kumjian, Lu, Verlinde, et al, , Oue, Kumjian, Lu, Jiang, et al, ). An example of multimodal spectra is shown in Figure a.…”
Section: Methodsmentioning
confidence: 99%
“…Schrom et al () suggested a polarimetric technique to separate contributions from aggregates and dendrites in the DGL of midlatitude winter storms. Polarimetric signatures of the secondary ice mixed with aggregated and rimed snow in layers with temperature around −5°C were found by cloud and precipitation radar measurements in high‐latitude deeper snow clouds (Oue, Kumjian, Lu, Verlinde, et al, ; Sinclair et al, ), midlatitude mesoscale convective systems (Giangrande, Toto, Bansemer, et al, ; Kumjian et al, ), and midlatitude snowstorms (Kumjian & Lombardo, ). However, combining polarimetric measurements with the analysis of Doppler spectra yields a much better chance to identify and separate different types of ice, and to quantify their amounts if their corresponding fall velocities are associated with separate peaks in the Doppler spectrum.…”
Section: Introductionmentioning
confidence: 96%